Recovery of metal values from copper smelter slags by roasting with pyrite - Tümen, Fikret; Bailey, N. Terry (My University, 1990)
Sulphation roasting of primary and secondary copper slags has been carried out to facilitate the dissolution of copper, nickel, cobalt, zinc and iron. The process comprised preroasting of the ground slag followed by roasting with pyrite and then leaching with water. The effects of the roasting and leaching conditions on the recovery of the metal values were explored. While a significant amount of copper solubilization was achieved by direct roasting of sulphidic primary slags, roasting with added pyrite increased the recovery. This technique also enabled the copper to be recovered from a secondary smelting slag. Under optimum conditions, more than 95% of copper could be recovered by only a limited recovery of cobalt, nickel and zinc could be achieved by roasting the preroasted slag with pyrite at 550°C for 1 h with a 0.25 pyrite/slag ratio. Around 2% of the iron in the slags was extracted into the leach solutions. An increase in the roasted temperature resulted in reduced iron contamination but the recovery of copper was also reduced. However, aeration seemed to be an appropriate way to reduce the iron contamination of the leach solutions.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Metal recovery; Pyrite; Sulphation roasting